The place of glucosylated enteral solution in the correction of hemorheological abnormalities in acute poisoning by psychopharmacological drugs - M. M. Potskhveriya; K. K. Ilyashenko; M. V. Belova; A. Yu. Simonova; E. E. Bitkova (Трансплантология (Москва))
Introduction. In acute exogenous poisoning, hemorheological abnormalities are observed. Various extracorporeal, physico-chemical methods are used to correct them. There is an opinion that the enteral route of administration of corrective agents may be a more physiological way to restore homeostatic imbalances.Aim. To conduct a comparative assessment of the effect of glucosylated enteral solution and standard infusion therapy on hemorheological abnormalities in acute poisoning by psychopharmacological drugs.Material and methods. Patients with acute poisoning by psychopharmacological drugs who were treated at the N.V. Sklifosovsky Research Institute for Emergency Medicine in 2017–2021 were examined. Of these, 23 people, in whose treatment the enteral correction program was used, made up the study group, and 22 patients (the comparison group) underwent a standard set of therapeutic measures. Indicators of hemorheological status were examined on the 1st, 3rd and 5th days against the background of ongoing therapy. Statistical data analysis was carried out using the Statistica 10 software package (StatSoft, Inc., USA).Results. The use of a glucosylated enteral solution led to a reduction in plasma viscosity under normal hematocrit conditions at all follow-up periods. In patients of both groups, there was a decrease in blood viscoelasticity under conditions of high shear potential at all stages of the study, which indicates impaired red blood cell deformability. This process was more pronounced in individuals of the comparison group. The conducted studies have shown that the use of infusion therapy and glucosylated enteral solution in the early stages of acute poisoning by psychopharmacological drugs generally has a unidirectional positive effect on hemorheological indicators, contributing to the stabilization of blood circulation. At the same time, the effect of glucosylated enteral solution therapy is faster and more pronounced.Conclusions. The use of glucosylated enteral solution and infusion therapy as a supportive treatment in the early period of acute poisoning by psychopharmacological drugs in most cases has a unidirectional effect on hemorheological parameters. In cases of glucosylated enteral solution therapy, there was an outrunning positive dynamics on the part of the majority of the studied hemorheological parameters. Glucosylated enteral solution can be the method of choice as a maintenance therapy after the end of detoxification process for acute poisoning by psychopharmacological drugs.